The roles of employees coaching towards employee outcomes / Nursaadatun Nisak Ahmad, Ida Rosnita Ismail and Azman Ismail - Ismail, Ida Rosnita; Ismail, Azman (Penerbit UiTM (UiTM Press), 2017)
Employees’ coaching is an effective management tool to enhance employees’ performance and development. Since 1980, a number of researchers have noted the value of the employees’ coaching relationship, but there is still little evidence regarding what makes employees’ coaching to be effective in Malaysia. Therefore, the study looked at the role of leader coach (supervisory coaching behaviour and autonomy support) toward enhancing employees’ motivation (employees’ self-efficacy) and performance to explore this topic in-depth. Again, the purpose of an immediate supervisor as a coach in a practice context is to help employees to consider how they might work and behave differently with a more effective behaviour and thus lead to better outcomes, without a reliance on the formal authority the manager possesses. The outcomes of using PLS-SEM path model analysis showed three important findings: First, the relationship between supervisory coaching behaviour was not correlated with employees’ self-efficacy. Second, autonomy support was positively correlated with employees’ selfefficacy; and third, employees’ self-efficacy indirectly influences employees’ performance.